Catalytic reductive deoxygenation of esters to ethers driven by hydrosilane activation through non-covalent interactions with a fluorinated borate salt. Issue 14 (26th June 2020) - Rysak, Vincent; Dixit, Ruchi; Trivelli, Xavier; Merle, Nicolas; Agbossou-Niedercorn, Francine; Vanka, Kumar; Michon, Christophe
Abstract : A fluorinated borate BArF salt catalyses the reductive deoxygenation of esters to ethers by using hydrosilanes. Experimental and theoretical studies highlight the role of noncovalent interactions in the reaction mechanism. Abstract : We report the catalytic and transition metal-free reductive deoxygenation of esters to ethers through the use of a hydrosilane and a fluorinated borate BArF salt as a catalyst. Experimental and theoretical studies support the role of noncovalent interactions between the fluorinated catalyst, the hydrosilane and the ester substrate in the reaction mechanism.